Interactive effects of carnitine status, dietary carnitine, and added fat on growth performance of weanling pigs - J C Woodworth; K Q Owen; J Lopez; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Two experiments were conducted to determine the interactive effects of carnitine status (with or without carnitine in diets fed to sows in gestation and lactation), and added fat and dietary carnitine in nursery diets on growth performance of weanling pigs. Feeding sows diets containing carnitine in gestation and lactation had no effect on growth performance of their pigs through 27-d after weaning. A carnitine by fat interaction (P<0.05) was observed for ADFI from d 0 to 7 and ADG from d 0 to 27 in Exp. 1 with pigs fed carnitine and no added fat appearing to have the best performance. In exp. 2, added carnitine had little effect on growth performance, whereas added fat improved feed efficiency. In conclusion, no benefit to growth performance was observed from adding both carnitine and fat to the diet of weanling pigs in these experiments.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Weanling pigs; Carnitine; Fat